Decomposition of dissolved organic contaminants by combining a boron-doped diamond electrode, zero-valent iron and ultraviolet radiation. (February 2019) - Sedlazeck, Klaus P.; Vollprecht, Daniel; Müller, Peter; Mischitz, Robert; Gill, Johanna; Trois, Wolfgang; Maunz, Ingomar; Frate, Roman; Mann, Oliver; Wruss, Klaus
Abstract: This study presents the results of a research project dealing with the degradation of dissolved tetrachloroethene, MTBE and clopyralid by using a boron-doped diamond electrode, zero-valent iron in a fluidized bed reactor and ultraviolet radiation. These treatment methods were tested alone, in any combination of two as well as in combination of all three of them to identify emerging synergy effects. Additionally, the influence of adding H2 O2 or H2 O2 + H2 SO4 is investigated. The experiments revealed that the treatment methods alone were able to decrease the organic contaminant concentrations, yet, the decomposition rate was not very sufficient. Applying the BDD yielded the highest decomposition rates, however, this degradation was accompanied by metabolite production. By combining two methods and adding H2 O2, the decomposition was enhanced significantly for any combination. These removal rates were further increased by using the combination of the three treatment methods and adding H2 O2 or H2 O2 + H2 SO4 . These high removal rates were not achieved by solely using the combination of the three methods without further addition of chemicals. This research demonstrates the potential, but also the limitations of the investigated system. Graphical abstract: Highlights: Combining a boron-doped diamond electrode, zero-valent iron and ultraviolet radiation. Combined three treatment methods for the degradation of dissolved organic compounds. Tetrachloroethene, MTBE and clopyralid were successfully removed from the waters. Treatment efficiency was significantly enhanced by adding H2 O2 or H2 O2 + H2 SO4 . Given thresholds were reached by using the combination and H2 O2 or H2 O2 + H2 SO4 .